5/#274 Is reflex MLH1 promoter hypermethylation testing following MLH1 loss by immunohistochemistry in endometrial carcinoma best practice?. (4th December 2022) - Plotkin, Anna; Olkhov-Mitsel, Ekaterina; Nofech-Mozes, Sharon
Abstract : Objectives: Reflex screening of newly diagnosed endometrial carcinomas (EC) was introduced in Ontario for women <70 in 2018 and regardless of age in 2020. MLH1 deficient (MLH1-d) cases by immunohistochemistry (IHC) are further analyzed to detect MLH1 promoter hypermethylation (MLH1PHM). Women with MLH1PHM tumors are considered at low risk for Lynch Syndrome and forgo referral to cancer genetic clinics. Regardless of MLH1PHM status, MLH1-d IHC helps to classify EC according to TCGA-based molecular classification and for consideration of immunotherapy. This study sought to examine the proportion of MLH1PHM in MLH1-d cases. Methods: Retrospective audit of pathology reports (2018–2021) in a major community laboratory in Ontario, Canada (Life Labs) identified EC samplings that were evaluated by IHC for MMR proteins (MLH1, MSH2, MSH6, and PMS2) followed by MLH1PHM test, when appropriate. Results: Among 1229 consecutive EC samples tested by MMR-IHC, 14 could not be classified due to insufficient tumor cells or ambiguous staining. The remaining 1215 ECs were classified into MMR-d (n=324, 26.7%) or proficient (n=891, 73.3%). Among MMR-d cases, 274 showed loss of MLH1 and 206 had available MLH1 methylation testing data. MLH1PHM was detected in 201/206 (97.6%), designated as most likely sporadic whereas 5/206 cases (2.4%) were not hypermethylated raising the possibility for Lynch syndrome. Conclusions: Our audit confirms the feasibility of testing endometrial samplings for MMR-IHC and promoter hypermethylation testing. MLH1PHM accounts for vast majority of MLH1/PMS2-deficient cancers in a universally screened EC population. The very high proportion of MLH1PHM challenges the practice algorithm and raises the need to explore practice revision.